FACTORS AFFECTING STUDENT INTEREST TO CONTINUE STUDYING ABROAD - Miftakhul Khoirun Niffa; Sukirno Sukirno (Jurnal Pendidikan Akuntansi Indonesia, 2018)
This study aimed to know the influence of (1) English Ability (2) Education Cost (3) Perception about Abroad Education Quality, and (4) English Ability, Education Cost, and Perception about the Quality of Education Abroad simultanously toward Interest to Continue Studying Abroad of Excellent Class Students of Economic Faculty Yogyakarta State University 2014. Data Collection Technique used in this research were documentation and questionnaire. Population of this research was the excellent class students of Economic Faculty YSU 2014. The research showed that there is a (1) positive and significant influence of English Ability toward Interest to Continue Studying Abroad 2) negative and significant influence of Education Cost toward Interest to Continue Studying Abroad, (3) positive and significant influence of Perception about Abroad Education Quality toward Interest to Continue Studying Abroad (4) influence of English Ability, Education Cost, and Perception about Abroad Education Quality simultanously toward Interest to Continue Studying Abroad. Keywords: Interest to Continue Studying Abroad, Education Cost, English Ability, Perception